2002
DOI: 10.1029/2001jd001297
|View full text |Cite
|
Sign up to set email alerts
|

Modification of spectral UV irradiance by clouds

Abstract: [1] Approximately 10,000 UV irradiance spectra resulting from 2 years of continuous measurements in Germany were used as a database to analyze the effect of cloudiness on spectral UV irradiance. Values of spectral cloud modification factors (CMF) were derived by modeling a corresponding clear-sky irradiance spectrum for every UV measurement under cloudy conditions. The total set of CMF values was used to train neural networks using different sets of input data ( parameter records) to describe the clouds, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 38 publications
0
60
0
3
Order By: Relevance
“…Kaurola et al, 2000;Schwander et al, 2002;Koepke et al, 2006). European Union's Action COST 726 identified global irradiance in combination with cloud modification factors (CMFs) as the best way to describe cloud attenuation and cloud effects on solar UV (Koepke et al, 2006).…”
Section: Cloudiness Global Irradiance and Sunshine Durationmentioning
confidence: 99%
“…Kaurola et al, 2000;Schwander et al, 2002;Koepke et al, 2006). European Union's Action COST 726 identified global irradiance in combination with cloud modification factors (CMFs) as the best way to describe cloud attenuation and cloud effects on solar UV (Koepke et al, 2006).…”
Section: Cloudiness Global Irradiance and Sunshine Durationmentioning
confidence: 99%
“…A method to reconstruct the UV in the Netherlands has been reported that employs the reduction by cloud in the global broadband solar radiation to determine the UV exposures (den Outer 2005). Schwander et al (2002) have integrated pyranometer broadband total solar irradiance and illuminance, measured by a Luxmeter, with the variables of SZA, ground albedo and cloud parameters. These were determined from visual observations of total cloud cover, cloud type (low, medium high and high) and solar disk obstruction, to determine the cloud modification factor (CMF) for the UV.…”
Section: Introductionmentioning
confidence: 99%
“…The clear-sky irradiance is either taken from measurements or it is modelled. The latter is preferred since appropriate corresponding values (at least in SZA, ozone amount, aerosol properties and surface albedo) are often not available [42]. The CMF is expected to be close to 1.0 for clear sky and no aerosols.…”
Section: Cloudsmentioning
confidence: 99%
“…This hypothesis, based on heat protection is not supported by physical arguments since a black body absorbs more energy, and, consequently, becomes warmer than a white body. 42 …”
Section: Protection Of Sweat Glands and Blood Vesselsmentioning
confidence: 99%